Wujud Kesantunan Berbahasa Mahasiswa Terhadap Dosen di STAIN Kendari: Kajian Sosiopragmatik - Fahmi Gunawan (JURNAL ARBITRER, 2013)
This article aims at describing the forms of politeness of the STAIN Kendari's students and their lecturers in interaction. The data are any utterances uttered in campus  by using descriptive-qualitative approach, it is a found that the students use some kinds of modes in implementing politeness. They are declarative and interogative sentence to express the politeness and imperetive for impoliteness. Besides, the use of complete sentence with commonly chronological order is indicating the politeness. The less complete sentence with inverisive order reflects the impoliteness.